Ossified Posterior Longitudinal Ligament With Massive Ossification of the Anterior Longitudinal Ligament Causing Dysphagia in a Diffuse Idiopathic Skeletal Hyperostosis Patient. Issue 32 (August 2015) - Murayama, Kazuhiro; Inoue, Shinichi; Tachibana, Toshiya; Maruo, Keishi; Arizumi, Fumihiro; Tsuji, Shotaro; Yoshiya, Shinichi; Bernhard, Schaller.
<x xml:space="preserve">Abstract</x> Abstract Descriptive case report. To report a case of a diffuse idiopathic skeletal hyperostosis (DISH) patient with both massive ossification of the anterior longitudinal ligament (OALL) leading to severe dysphagia as well as ossification of the posterior longitudinal ligament (OPLL) causing mild cervical myelopathy, warranting not only an anterior approach but also a posterior one. Although DISH can cause massive OALL in the cervical spine, severe dysphagia resulting from DISH is a rare occurrence. OALLs are frequently associated with OPLL. Treatment for a DISH patient with OPLL in setting of OALL-caused dysphagia is largely unknown. A 70-year-old man presented with severe dysphagia with mild cervical myelopathy. Neurological examination showed mild spastic paralysis and hyper reflex in his lower extremities. Plane radiographs and computed tomography of the cervical spine revealed a discontinuous massive OALL at C4-5 and continuous type OPLL at C2-6. Magnetic resonance imaging revealed pronounced spinal cord compression due to OPLL at C4-5. Esophagram demonstrated extrinsic compression secondary to OALL at C4-5. We performed posterior decompressive laminectomy with posterior lateral mass screw fixation, as well as both resection of OALL and interbody fusion at C4-5 by the anterior approach. We performed posterior decompressive laminectomy with posterior lateral mass screw fixation, as well as both resection of OALL and interbody fusion at C4-5 by the anterior approach. Severe dysphagia markedly improved without any complications. We considered that this patient not only required osteophytectomy and fusion by the anterior approach but also required decompression and spinal fusion by the posterior approach to prevent both deterioration of cervical myelopathy and recurrence of OALL after surgery.